Integrating YouTube Digital Media in Early Childhood Education for Introducing Dompu Local Culture - Cici Muliati; Ihlas Ihlas; Muslim Muslim (Journal of Islamic Education Students (JIES), 2026)
This study aims to analyze the use of YouTube digital media as a means of introducing the local culture of the Dompu community in early childhood in PAUD Amalia Kreatif. The development of digital technology provides opportunities for early childhood education institutions to utilize audiovisual media in the learning process, especially in introducing local cultural values from an early age. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects include teachers and students at PAUD Amalia Kreatif. The results of the study show that the use of YouTube media can increase children's interest in learning, make it easier for children to understand local cultural elements such as dance, traditional clothing, regional languages, and the traditions of the Dompu people. In addition, audiovisual media helps teachers convey material in a more interesting, interactive, and contextual way. However, the use of digital media still requires teacher assistance so that the content presented is appropriate for the child's age and learning goals. Thus, the use of YouTube can be an effective alternative learning media in introducing local culture to early childhood while supporting the preservation of regional culture.